Kinetics of alkene formation in the homogeneous and in the heterogeneously catalysed methanolyses of 2-bromo-2-methyl propane (t-butyl bromide) - Roger J. Mortimer; Michael Spiro (1982)
The kinetics of the methanolysis of 2-bromo-2-methylpropane have been studied from 25 to 40 °C by a pH-stat method and the products analysed chromatographically. In dilute solutions both alkene and ether formation increased steadily with time but in concentrated solution the alkene concentration passed through a maximum. This allowed the rate constant of the acid-catalysed methanolysis of 2- methylprop- 1 -ene to be calculated. Addition of sodium methoxide to concentrated t-butyl bromide increased the alkene yield by E2 elimination. However, in the presence of silver bromide the percentage of alkene fell sharply while the rate of ether formation markedly increased. On the silver bromide surface the t-butyl bromide solvolysed ca. 105 times faster than in the bulk methanol solution.